Genome Mapping Application in Diagnosis and Treatment of different Cancers - Xiao, Zhiwen (International Journal of Psychosocial Rehabilitation, 2019)
A wide range of cancer risk factors acts as mutagens and contributes to mutations in human body cells, some might cause carcinogenesis in cells, and then lead to the development of malignancies. Mutations occur in different cancers that can be in various forms, for instance, some contain gene amplification, but some have gene deletion. Doctors always seek to identify those essential genetic mutations in cancers for diagnosis and treatment, but those mutations increase as cancer cells develop over time, for example, metastasizing from primary sites to secondary sites. Genome mapping on cancers via different techniques are developed to be used as indicators of mutated genes, cancer genomes, therefore, provide new data for diagnosis and treatments of this disease, which assists pharmaceutical advancing on targeted therapy for treating specifically on gene mutations. Although genome mapping is helpful, there are ethical issues appear as well, which genome information can be considered as personal privacies. This review introduces mutation types in cancer as well as cancer risk factors, and how some of those mutations can be diagnosed by genome mapping, which focuses particularly on three methods in terms of their principles and how some of those are applied to diagnosis and drug development on four types of cancer.